2009
DOI: 10.1111/j.1365-3059.2009.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide sensitivity in Swedish isolates of Phaeosphaeria nodorum

Abstract: This is the first report of variability in sensitivity of Phaeosphaeria nodorum to the fungicide azoxystrobin, and also reports on sensitivity to propiconazole, prothioconazole and cyprodinil. An in vitro sensitivity test of 42 isolates from five Swedish winter wheat fields, collected in 2003 -2005, was performed on malt extract agar amended with six concentrations of each fungicide. Four isolates collected during the early 1990s, before azoxystrobin had been commercially used in agriculture, were used as refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Further validation was carried out by making model predictions for 16 cases of resistance that were not included in the dataset used for deriving the model. These 16 cases comprised 11 cases that were not included originally because they were lacking active substance molecular complexity information (cases 3, 22, 27, 30, 31, 33, 37, 54, 55, 56 and 59) and a further five cases identified from the literature after the model was completed. Summary information for these five cases are given as case numbers 62 to 66 in Table , and the trait values and categories used to predict FDR time are given in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…Further validation was carried out by making model predictions for 16 cases of resistance that were not included in the dataset used for deriving the model. These 16 cases comprised 11 cases that were not included originally because they were lacking active substance molecular complexity information (cases 3, 22, 27, 30, 31, 33, 37, 54, 55, 56 and 59) and a further five cases identified from the literature after the model was completed. Summary information for these five cases are given as case numbers 62 to 66 in Table , and the trait values and categories used to predict FDR time are given in the supporting information.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of mutation in each resistant isolate was checked as previously described . The DNA of each fungi was extracted using the PrepMan Ultra Reagent (Applied Biosystems, Waltham, USA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The DNA of each fungi was extracted using the PrepMan Ultra Reagent (Applied Biosystems, Waltham, USA) according to the manufacturer's instructions. PCR amplification of the CytB gene was carried out using the Ex Taq Kit (Takara, Kyoto, Japan) based on the previously described methods for each pathogen species . DNA sequencing was also performed according to the method described in previous reports .…”
Section: Methodsmentioning
confidence: 99%
“…The rapid increase of the frequency of the mutations F129L and G143A in pathogen population was observed and in 2005 both mutations were found in a significant proportion of the isolates from Sweden, Denmark and Germany (Sierotzki et al, 2007). A first report of variability in sensitivity of P. nodorum to azoxystrobin was made by Blixt et al (2009). In the majority of the P. nodorum isolates, collected in [2003][2004][2005] in Sweden, the mutation G143A, associated with loss of sensitivity to strobilurins was found.…”
Section: Ratementioning
confidence: 99%
“…In order of precedence between DMI fungicides in 1994 epoxyconazole showed the best efficacy against Septoria both M. graminicola and P. nodorum (Kendall & Hollomon, 1994). Still recent epoxyconazole and prothioconazole are referred as very effective in controlling M. graminicola (Cools & Fraaije, 2008 (Blixt et al, 2009). The results of semi-field trial carried out in Denmark showed that propiconazole + fenpropimorf had only a residual preventive effect for 10 days in comparison to azoxystrobin, which showed a very effective, long preventive effect against P. nodorum, lasting for three weeks or more, however against M. graminicola both propiconazole and azoxystrobin had a similar curative effect (Jorgensen et al, 1999).…”
Section: Ratementioning
confidence: 99%